Two-stage calibration of a 6-axis force-torque sensor for robust operation in the Mars 2020 robot arm. (17th November 2021) - Schaler, Ethan W.; Wisnowski, James; Iwashita, Yumi; Edlund, Jeffrey A.; Sly, Jacqueline H.; Raff, William; Kriechbaum, Kristopher L.; Frost, Matthew A.; McCormick, Ryan L.; Townsend, Julie A.
ABSTRACT: A main objective of the Mars 2020 rover mission (Perseverance) is to collect and preserve samples of rock and soil from the Martian surface. To accomplish this task, the Perseverance Rover carries a Sampling and Caching Subsystem outfitted with Coring Drill mounted on a 5 degree-of-freedom (DoF) robotic arm. Safe operation of the Robotic Arm and its tools relies on force feedback, provided by a custom Force-Torque Sensor (FTS) which is positioned to sense end-effector external loads. This work describes the methods and algorithms used in the calibration of the Robotic Arm FTS to achieve the required force-feedback accuracy over all expected Mars and Earth operating environments. Specifically, we use a two-stage, least-squares optimization process to generate an FTS calibration model that is fit to both sensor-level and system-level calibration data, while implicitly compensating for offset, scaling, and thermal errors observed during sensor integration into the robotic arm system. This technique is compatible with remote FTS re-calibration while the rover is operating on Mars. Data collection strategies, standalone versus system-integrated sensor findings, results of validation exercises in Earth-ambient and Mars-like environments, and initial FTS commissioning data on Mars are all included. GRAPHICAL ABSTRACT: UF0001